GENETIC DIVERSITY AND RANDOM AMPLIFIED POLYMORPHIC DNA ANALYSIS OF PESTALOTIA SP. ISOLATES OF ENDOPHYTES FROM DIFFERENT HOST - Arvindganth, Rajasekar; Kathiravan, Govindarajan; Thilagavathi, Thirugnanasambandam; B, Varsha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The genetic diversity of fungal endophytes medicinally important plant leaves. Isolates fungi were genotypically compared by random amplified polymorphic DNA (RAPD) techniques. The results indicate that RAPD can be employed for detecting genetic diversity of Pestalotia species from medicinal plants and for pre-selection of these isolates for bioactive screening program. Methods: Using different instrumental methods for isolation and identification of bioactive compounds and RAPD molecular method for detection of taxol producing fungi. Results: Our studies also suggest diversity of endophytes as it differs in plant diversity. Pestalotia spp. are of considerable interest to researchers and pharmacists due to their capabilities of synthesizing a wide range of economically important bioactive molecules. Conclusion: RAPD markers did not differentiate and place the isolates into respective host or locations from which they were isolated. The relationship between species isolated from the same or different hosts do not support phylogenetic analysis and also morphologically similar species form close relationships rather than the isolates of the same host. Keywords: Genetic diversity, Endhophytic fungi, Pestslotia sp., Random amplified polymorphic DNA.